Comparison of sodium alginate-based and sodium hyaluronate-based submucosal injection materials based on rheological analysis. (December 2021) - Hirose, Ryohei; Watanabe, Naoto; Naito, Yuji; Hashimoto, Hikaru; Sugino, Satoshi; Yoshida, Takuma; Bandou, Risa; Daidoji, Tomo; Inoue, Ken; Dohi, Osamu; Yoshida, Naohisa; Nakaya, Takaaki; et al.
Abstract: As a viscous high-performance submucosal injection material (SIM) used in endoscopic submucosal dissection (ESD), sodium alginate-based SIM (SA-SIM) was recently introduced as high-performance SIM equivalent to sodium hyaluronate-based SIM (HA-SIM) in Japan. However, a comprehensive, detailed comparison of SA and HA is yet to be performed. In this study, we precisely measured the viscoelastic properties, submucosal elevation height (SEH), and injection pressure (IP). Furthermore, we compared the outcomes of ESD using an ex vivo ESD model. There was no significant difference in SEHs between HA-SIM and SA-SIM at all post-injection times, and the IP of the SA-SIM injection was significantly higher than that of the HA-SIM injection in all conditions (P < 0.0001). The viscosity at high shear rates of SA-SIM was higher than that of HA-SIM; this result was consistent with SEH/IP measurement results. No significant difference was observed in ESD procedure time and total volume of injected SIM between HA-SIM and SA-SIM (18.1 ± 6.7 and 17.8 ± 6.0 min, P = 0.8987; 13.3 ± 5.3 and 11.6 ± 5.9 ml, P = 0.4658, respectively). Although SA-SIM was slightly more difficult to inject than HA-SIM, there was no significant difference in performance between the materials. Thus, this basic study demonstrated that SA-SIM can be used for endoscopic treatment as well as HA-SIM, and supported previous clinical research data. Highlights: The viscosity of SA-SIM at high shear rates was higher than that of HA-SIM. The IP of SA-SIM injection was significantly higher than that of HA-SIM injection. There was no significant difference in SEHs between HA-SIM and SA-SIM. No significant difference was observed in ESD outcomes between HA-SIM and SA-SIM.